Analisis Penerapan Akuntansi Murabahah Dalam Pembiayaan KPR Syariah Ditinjau Dari PSAK No.102 Pada Bank Syariah Indonesia - Nirmadarningsih Hiya; Saparuddin Siregar; Sanusi Gazali Pane (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to analyze the application of murabahah contracts in Sharia mortgages and adjust PSAK No. 102 Revision 2019 regarding murabahah accounting at the Medan Islamic Bank Branch. This study used descriptive qualitative method. The data collection technique in this study was in the form of interviews and some secondary data in the form of financial statement documents obtained from the Medan Islamic Bank Branch. The results of the research on the application of the murabahah contract on Sharia mortgages have been in accordance with what has been determined. Meanwhile, the implementation of murabahah financing is not fully in accordance with PSAK No. 102 Revision 2019 at Bank Syariah Indonesia Medan Branch such as banks only apply murabahah financing based on orders only, meaning that, in PSAK 102 it is stated that murabahah can be carried out based on orders or without orders, in fact the Bank Syariah Indonesia Medan Branch only applies murabahah based on orders.